Finding common ground grassroots dialogue principles for interreligious learning at university - Cronshaw, Darren (2021)
Finding Common Ground (FCG) is an interreligious dialogue program hosted in the Multi Faith Facility of Swinburne University of Technology. This article evaluates the interreligious learning elements as one aspect of the program’s social inclusion and intercultural literacy objectives. The grassroots dialogue principles that FCG follows are ground rules of respect, story-sharing of religious experience, compassionate listening, valuing difference with curious questions, and identifying sources of strengths and courage. The experience of Swinburne FCG participants illustrates how these dialogue principles can best facilitate interreligious learning.
Keywords: Cultural Diversity; Higher Education; Interfaith Dialogue; Interreligious Learning; Religious Experience